A high force of plasmodium vivax blood-stage infection drives the rapid acquisition of immunity in papua new guinean children. - Cristian Koepfli; Kathryn L Colborn; Benson Kiniboro; Enmoore Lin; Terence P Speed; Peter M Siba; Ingrid Felger; Ivo Mueller (Public Library of Science (PLoS), 2013)
When both parasite species are co-endemic, Plasmodium vivax incidence peaks in younger children compared to P. falciparum. To identify differences in the number of blood stage infections of these species and its potential link to acquisition of immunity, we have estimated the molecular force of blood-stage infection of P. vivax ((mol)FOB, i.e. the number of genetically distinct blood-stage infections over time), and compared it to previously reported values for P. falciparum.P. vivax (mol)FOB was estimated by high resolution genotyping parasites in samples collected over 16 months in a cohort of 264 Papua New Guinean children living in an area highly endemic for P. falciparum and P. vivax. In this cohort, P. vivax episodes decreased three-fold over the age range of 1-4.5 years.On average, children acquired 14.0 new P. vivax blood-stage clones/child/year-at-risk. While the incidence of clinical P. vivax illness was strongly associated with mol FOB (incidence rate ratio (IRR) = 1.99, 95% confidence interval (CI95) [1.80, 2.19]), (mol)FOB did not change with age. The incidence of P. vivax showed a faster decrease with age in children with high (IRR = 0.49, CI95 [0.38, 0.64] p<0.001) compared to those with low exposure (IRR = 0.63, CI95[0.43, 0.93] p = 0.02).P. vivax (mol)FOB is considerably higher than P. falciparum (mol)FOB (5.5 clones/child/year-at-risk). The high number of P. vivax clones that infect children in early childhood contribute to the rapid acquisition of immunity against clinical P. vivax malaria.